Prediction of Salmon Inhibitor Peptides For DPP-IV Proteins Using Molecular Docking - Nahdiyah Vernanda Saputri; Yulanda Antonius (Jurnal Biologi Tropis, 2026)
Diabetes mellitus is the 3rd leading cause of death in Indonesia. Glucagon like peptide-1 (GLP-1) and gastric inhibitory polypeptide (GIP) are incretin hormones that function in postpandrial insulin secretion. The purpose of this study was to determine potential peptides from salmon as DPP-IV inhibitors for antidiabetic drugs, using the molecular docking method. This study design refers to several in silico peptide design studies through a bioinformatics approach. The results showed that bioactive peptide molecules derived from salmon, as well as peptide 1 and peptide 2 were predicted as potential molecular peptides and had good interactions with DPP-IV proteins, and were proven to be able to inhibit the DPP-IV enzyme as a target for diabetes mellitus drugs through the identification and evaluation of molecular interactions that occurred using the in silico peptide protein-based molecular binding method. The conclusion is that bioactive peptide molecules derived from salmon, as well as peptide 1 and peptide 2 were predicted as potential molecular peptides and had good interactions with DPP-IV proteins and were proven to be able to inhibit the DPP-IV enzyme.